Experimental Horizontal Transmission of Enterospora nucleophila (Microsporea: Enterocytozoonidae) in Gilthead Sea Bream (Sparus aurata) - Amparo Picard-Sánchez; M. Carla Piazzon; Itziar Estensoro; Raquel Del Pozo; Nahla Hossameldin Ahmed; Oswaldo Palenzuela; Ariadna Sitjà-Bobadilla (Animals, 2021)
Enterospora nucleophila is a microsporidian enteroparasite that infects mainly the intestine of gilthead sea bream (Sparus aurata), leading to an emaciative syndrome. Thus far, the only available information about this infection comes from natural outbreaks in farmed fish. The aim of the present study was to determine whether E. nucleophila could be transmitted horizontally using naturally infected fish as donors, and to establish an experimental in vivo procedure to study this host–parasite model without depending on natural infections. Naïve fish were exposed to the infection by cohabitation, effluent, or intubated either orally or anally with intestinal scrapings of donor fish in four different trials. We succeeded in detecting parasite in naïve fish in all the challenges, but the infection level and the disease signs were always milder than in donor fish. The parasite was found in peripheral blood of naïve fish at 4 weeks post-challenge (wpc) in oral and effluent routes, and up to 12 wpc in the anal transmission trial. Molecular diagnosis detected E. nucleophila in other organs besides intestine, such as gills, liver, stomach or heart, although the intensity was not as high as in the target tissue. The infection tended to disappear through time in all the challenge routes assayed, except in the anal infection route.